A duális szakképzés gyakorlata győri autóipari vállalatoknál - Pongrácz Attila (Közép-európai közlemények, 2014)
It is the creation and broadening of the dual education system that has been in the focus of the transformation and development of the national vocational system in the past few years. More and more students this formation model in Hungary – not only in secondary education, but in higher ones as well. This formation system does not appear to be another short-lived fashionable trend of the educational policy, but much rather a serious teaching system that goes back to both national and European antecedents and is capable of meeting the requirements and challenges of today’s labour market. Such efforts have been proven by the labour market, too, since acquiring up-to-date and competitive technical professional knowledge at a concrete (producing) eneterprise while studying will considerably increase skilled labourers’ chances to find employment. In Győr, there are several enterprises of automotive industry determinant on both national and international levels that are leading in realizing, implementing and assisting or supporting dual vocational education and training. In this study of ours we give a brief summary on both the historical and legal background of the dual vocational education and training, present the main points of the student–parent–employer co-operation as well as the local experience gained on this practice-oriented model – based on concrete and factual company examples.